Switzerland : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper attempts to quantify the impact of the demographic shift on growth and public finances in Switzerland. It examines the intertemporal consistency between current policy plans and unfunded liabilities, focusing primarily on social security, and explores policy options. It finds that so far, the impact of aging on the economy has been moderate. The number of pensioners has risen in recent years, but this is mainly owing to early retirees taking advantage of the generous disability and pension systems. The paper also examines the need for health care reforms in Switzerland.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet